Praktik Suap di Birokrasi Pemerintahan Perspektif Tafsir Ahkam Al-Jinaiyyah - Marpaung, Zaid Alfauza; Yuslem, Nawir; Hamdani, Muhammad Faisal (Universitas Medan Area, 2023)
The contemporary challenge faced by governmental bureaucracy revolves around the pervasive issue of corruption, particularly bribery. This research aims to scrutinize bribery practices within governmental bureaucracy through the lens of the tafsir ahkam al-jinaiyyah perspective, which is associated with the issue of bribery. The methodology employed is normative legal research with an Islamic legal concept approach, referencing the Quran and Hadith, subsequently analyzed qualitatively. Research findings indicate that bribery practices within the governmental bureaucracy, within the context of Islamic teachings, are considered acts of